2021
DOI: 10.5114/wiitm.2021.105528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different anesthetic methods on immune function and oxidative stress in patients undergoing laparoscopic herniorrhaphy.

Abstract: Introduction The influence of anesthetic method on the immune function and oxidative stress in patients receiving laparoscopic herniorrhaphy remains largely unknown. Aim To assess the effects of different anesthetic methods on the immune function and oxidative stress in patients undergoing laparoscopic herniorrhaphy. Material and methods A total of 280 eligible patients were randomly divided into two groups to receive total intravenous anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Similar favorable long-term outcomes with propofol-TIVA have also been found in patients undergoing gastrectomy and colectomy in the studies of Zeng et al (2018) [57] and Wu et al (2018) [58] respectively. In their article, Wu et al (2021) [59] discussed the impact of various anesthetic techniques on immune function and oxidative stress in patients undergoing laparoscopic herniorrhaphy. The authors found that, in comparison to intravenous anesthesia (IA), TIVA had a lesser impact on immune function and oxidative stress in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar favorable long-term outcomes with propofol-TIVA have also been found in patients undergoing gastrectomy and colectomy in the studies of Zeng et al (2018) [57] and Wu et al (2018) [58] respectively. In their article, Wu et al (2021) [59] discussed the impact of various anesthetic techniques on immune function and oxidative stress in patients undergoing laparoscopic herniorrhaphy. The authors found that, in comparison to intravenous anesthesia (IA), TIVA had a lesser impact on immune function and oxidative stress in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In their article, Wu et al . (2021) [ 59 ] discussed the impact of various anesthetic techniques on immune function and oxidative stress in patients undergoing laparoscopic herniorrhaphy. The authors found that, in comparison to intravenous anesthesia (IA), TIVA had a lesser impact on immune function and oxidative stress in these patients.…”
Section: Discussionmentioning
confidence: 99%